2022
DOI: 10.1007/s12072-022-10456-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for portopulmonary hypertension in patients with cirrhosis: a prospective, multicenter study

Abstract: Background Measurement of the tricuspid regurgitation pressure gradient (TRPG) by echocardiography is recommended as the most objective examination for the detection of portopulmonary hypertension (PoPH). This prospective study aimed to identify factors associated with a high TRPG in patients with cirrhosis and develop a screening method for identifying patients most likely to bene t from investigation with echocardiography.Results Four hundreds and eighty-six patients with cirrhosis underwent Doppler echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…According to a previous study, 5 the cut‐off mPAP value of 25 mmHg on right heart catheterization corresponds approximately to the cut‐off TRPG value of 35 mmHg on echocardiography. We have reported that TRPG ≥35 mmHg is associated with female sex, shortness of breath, and brain natriuretic peptide (BNP) ≥48.9 pg/mL and suggested that patients with these factors should undergo echocardiography 6 . However, this cut‐off TRPG value needs to be re‐established with the publication of the 2022 ESC/ERS criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous study, 5 the cut‐off mPAP value of 25 mmHg on right heart catheterization corresponds approximately to the cut‐off TRPG value of 35 mmHg on echocardiography. We have reported that TRPG ≥35 mmHg is associated with female sex, shortness of breath, and brain natriuretic peptide (BNP) ≥48.9 pg/mL and suggested that patients with these factors should undergo echocardiography 6 . However, this cut‐off TRPG value needs to be re‐established with the publication of the 2022 ESC/ERS criteria.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that TRPG ≥35 mmHg is associated with female sex, shortness of breath, and brain natriuretic peptide (BNP) ≥48.9 pg/mL and suggested that patients with these factors should undergo echocardiography. 6 However, this cut‐off TRPG value needs to be re‐established with the publication of the 2022 ESC/ERS criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies indicate the synthetic dysfunction is more severe among those with PoPAH than those with SchHSD. 7 , 19 , 20 However, hepatocellular injury severity is not associated with the development of PoPAH ( Table 1 ) and, more specifically, the Model for End-Stage Liver Disease score does not correlate with the incidence of PoPAH. 7 , 21 Furthermore, PoPAH can complicate liver diseases that have relatively little hepatocellular dysfunction.…”
Section: Schpah and Popah Commonalitiesmentioning
confidence: 96%